The perspectives of autologous hepatocytes generation for the treatment of liver failure - M. N. Evseeva; A. F. Sheptulina; Yu. P. Rubtsov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
The aim of the review. To analyze the main cellbased sources of hepatocyte for artificial liver generation, to describe the key features of each approach, to discuss benefits and shortcomings.Summary. Artificial liver transplantation could be an alternative for traditional transplantation. For the artificial liver generation specialized cells are required. So far several sources of hepatocyte-like cells generation are known. This review presents alternative approaches for liver failure treatment: inhibition of epithelial-mesenchymal transformation, e.g. by induction of proliferation (gene therapy with HGF), and by influence on immune imbalance (T-regulatory lymphocytes application).Conclusion. Evaluation of the main sources of autologous hepatocytes would provide insights into priority directions of future studies, and lead to progress in liver failure treatment.